Saving behaviour among generation Y in banking sector in Malaysia - Lina Adilah, Sahidan (2016)
This study is to shed a light the saving behavior among generation y in banking sector in Malaysia and to fill the knowledge gap on their saving behavior by looking into their saving behavior as well as their demographic characteristics. The purpose of this study is to identify whether there is a significant relationship between saving behavior and its determinants which consists of financial literacy, retirement planning behavior and debt management among Generation Y in Banking Sector in Malaysia. This research adopts quantitative approach where data for these studies has been conducted by survey method generation y in banking sector those ages between 19 -35 years old. A total of 150 set of questionnaire has been collected manually responded in 7 divisions in Maybank Corporate Banking which are MDO, SL, COS, CCS, Region, SER & EU. The finding from this study shows that Retirement Planning Behavior has the most influenced factor that influence saving behavior among Gen Y.